F. M. DOSTOYEVSKY AND L. N. TOLSTOY ABOUT SPIRITUALITY - S. V. Strutsenko (Obrazovanie i Nauka)
The paper is devoted to the urgent issue of moral personality formation in the framework of the modern education system. Both the society and education specialists are concerned about the unsatisfactory moral education of the growing generation. For solving the problem of moral revival, the author considers the Russian pedagogical heritage – particularly, the philosophical and publicistic works of F. M. Dostoyevsky and L. N. Tolstoy. The paper provides the modern definition of spirituality as the intellectual essence of the human being, based both on the deep knowledge of nature, society, human individuality and humanistic or religious values outweighing the selfish needs. In author’s opinion, the pedagogical concepts developed by Dostoyevsky and Tolstoy are still relevant, being aimed at developing the free personality and addressing the universal human values. The ideas and concepts of the 19th century’s outstanding thinkers perfectly correspond with the currently proclaimed educational content: they define the man as the highest society value; direct all the principles and parenting practices of spiritual and ethic education at creativity development, self-development, and self-improvement; and acknowledge a student’s individuality.